Survival of M1a Non-Small Cell Lung Cancer Treated Surgically: A Retrospective Single-Center Study - Liu, Tieqin; Liu, Hongxu; Wang, Gebang; Zhang, Chenlei; Liu, Bingbing (The Thoracic and Cardiovascular Surgeon, 2015)
Background Stage IV non-small cell lung cancer (NSCLC) is always associated with a poor outcome and is rarely treated with surgical resection. The aim of this study was to retrospectively analyze the effectiveness of surgical treatments.Methods We have retrospectively analyzed the records of NSCLC patients with local thoracic metastatic disease (M1a) who had been treated with surgical resection. The impact on survival of eight variables (age, gender, smoking status, current drinking status, site of metastasis, pathology classifications, resection status, and presence of adjuvant treatment) were further assessed.Results Eighty patients (49 males, 61%) with a median age of 58 (range, 38–80) were included. Metastatic sites included: pleural nodules with or without effusion metastasis (51, 63.8%), pleural effusion without nodules (7, 8.8%), contralateral lung (9, 11.3%), diaphragm nodules metastasis (5, 6.3%), and pericardium nodules metastasis (8, 10%). Histology was adenocarcinoma in 55, squamous-cell carcinoma in 16, large cell in 5 and other in 4 patients. Types of lung resection performed for primary tumors were complete resection in 43 and limited resection in 37 patients. Survival at 5 years for the overall population reached 31% (95% confidence interval, 19.4–43%). The median overall survival time was 34.3 months. Ten (12.5%) patients survived for more than 5 years. Smoking status and postoperative adjuvant treatment were independent prognostic factors (p = 0.006 and 0.013). There was no impact on survival for the other six variables.Conclusion Surgical treatments in M1a NSCLC seem to be associated with improved survival than published results and might be considered in the management of selected cases. Selected patients, including good performance status and nonsmoking histology, may predict for improved survival in these patients.
Keywords: local metastasis; non-small cell lung cancer; surgical resection